Pathogenesis : how germs made history - Kennedy, Jonathan (Great Britain : Penguin Random House, 2023)
"According to the accepted narrative of progress, a few great humans have bent the arc of history. But in this revelatory book, Dr Jonathan Kennedy argues that germs have done more to shape humanity at every stage, from the first success of Homo sapiens over the equally intelligent Neanderthals to the fall of Rome and the rise of Islam. How did an Indonesian volcano help cause the Black Death, setting Europe on the road to capitalism? How could 168 men extract the largest ransom in history from an opposing army of eighty thousand? And why did the Industrial Revolution lead to the birth of the modern welfare state? The latest science reveals that infectious diseases are not just something that happens to us, but a fundamental part of who we are. Indeed, the only reason humans don't lay eggs is that a virus long ago inserted itself into our DNA, and there are as many bacteria in your body as there are human cells. We have been thinking about the survival of the fittest all wrong: evolution is not simply about human strength and intelligence, but about how we live and thrive in a world dominated by microbes. By exploring the startling intimacy of our relationship with infectious diseases, Kennedy shows how they have been responsible for some of the seismic revolutions of the past 50,000 years. Provocative and brimming with insight, Pathogenesis transforms our understanding of the human story, revealing how the crisis of a pandemic can offer vital opportunities for change."--
Keywords: Pathology; Communicable diseases--Pathogenesis; How germs made history